Analysis Business Plan and Business Feasibility Studies To Interested Student Becomes Young Entrepreneurs In Program Study Management Faculty of Social Sciences Universitas Pembangunan Panca Budi - MIRA, Mira Yosefa Siregar Yosefa (Universitas Negeri Medan, 2022)
Mira Yosefa Siregar Manajemen,UniversitasPembangunan, Panca Budi, MEDANmirayosefas@yahoo.com Abstract. There companies that produce products and services the business competition its more complex, so that more competitors there, ways entrepreneurs can attract consumers to buy products or services that are sold according to their wants and needs. The importance of understanding business planning so that business can be carried out on the right track because it’s a guideline to sharpen the plans that are expected to be in accordance with the goals to be achieved. A good business plan has stages that must be done to maximize business opportunities, which is to seek business assistance funds. Information from the business plan includes the vision, mission and business objectives, financial reports, marketing strategies and detailed data sales The understanding of business feasibility studies is related to business planning due to assessing whether or not it is appropriate for a business to be established an existing business in order to compete in the current market share. Students' interest in becoming young entrepreneurs is considered good because students as the younger generation must have a high spirit, be productive, and can be a pioneer in the world of entrepreneurship in Indonesia, especially at the University Pembangunan Panca Budi, Medan.The research aims to determine how students' understanding of business plann, and business feasibility studies relate to their interest in becomes young entrepreneur. This study uses a qualitative method with the type of description. The subjects of this study were students who were trained in the two-class business feasibility study course totaling 60 people with the sampling technique being the sensus sample. Technical analysis data by collecting data, presenting data and conclusions. The results of the study found that there were supporting and inhibiting factors in the process of delivering material and business interests, for the supporting factors were having agile and responsive human resources, adequate facilities and infrastructure, financial conditions supporting the learning process at UNPAB, participating in extracurricular activities, lecturers giving assignments to students. While the inhibiting factors are the attitude of students who are not enthusiastic, lack of interest in learning and entrepreneurship, environmental factors of residence and friendship, low quality of lecturers without training and knowledge development and low student achievement. Guidance and motivation are needed for students to be motivated and have high competitiveness in facing the digital-based business world in the future with the progress of the industrial revolution 4.0. Keywords: Business Plan, Business Feasibility Study, Business Interest, Young Entrepreneurs